El desafio de la transicion de las pruebas de papel y lapiz a las pruebas computarizadas - Buško, Vesna (2010)
The presentation focuses on prospects of moving from paper-and-pencil to computer-based testing pointing also at basic conditions required to facilitate decision-making and bring about desired changes in the assessment, and consequently in teaching practices and essential learning and educational outcomes. Prevailing practices in psychological assessment and testing in Croatia will shortly be outlined. Current state of psychological and educational assessment including dominant areas, purposes and mode of testing will be noted. Potential barriers in implementing ICT in the assessment processes are discussed including knowledge / informational, organizational, policy, and financial issues. The reflections on benefits and likely obstacles to transition to computer based assessment will be exemplified by recent experiences from large-scale testing projects like national curriculum tests and PISA in Croatia.
Projekt MZOS
ENG